Case report: Gastric metastasis of breast cancer - Zhao, Qiandi; Zhang, De (Frontiers in Oncology, 2024)
Breast cancer stands as the foremost malignant tumor among women globally, with postoperative recurrence and metastasis significantly impacting patient prognosis. While metastasis to various sites has been reported, gastric involvement remains uncommon. Presenting a case of gastric metastasis a decade post-breast cancer surgery, we underscore the rarity of this occurrence. Our patient, an elderly woman, underwent left breast modified radical surgery ten years prior, followed by adjuvant chemotherapy, maintaining favorable health until experiencing abdominal discomfort two months ago. Contrast-enhanced computed tomography (CT) of the chest and upper abdomen unveiled diffuse abnormal enhancement in the gastric body and sinus wall. Subsequent gastroscopy revealed an ulcer near the gastric antrum, with immunohistochemical staining confirming invasive lobular carcinoma metastasis from the breast. We further conducted an extensive review of 23 cases with detailed information retrieved from PubMed, elucidating clinicopathological, endoscopic features, diagnostic modalities, and contemporary treatment strategies for breast-stomach metastasis. Our findings underscore the imperative of regular postoperative surveillance for breast cancer patients. Timely detection, accurate diagnosis, and appropriate intervention are paramount in managing gastric metastasis, significantly influencing patient outcomes.